Communication and role clarity inform TeleICU use: a qualitative analysis of opportunities and barriers in an established program using AACN framework - Anna Krupp; Michael Di Martino; Wesley Chung; Krisda Chaiyachati; Anish K. Agarwal; Ann Marie Huffenberger; Krzysztof Laudanski (BMC, 2021)
Abstract Background Understanding the use of tele-intensive care unit (ICU) services is an essential component in evaluating current practice and informing future use as the adoption and application of teleICU services expands. We sought to explore if novel ways to utilize teleICU services can emerge within an established, consulting-style teleICU model considering the program's flexible, provider-driven operation. Methods This was a qualitative study of one teleICU/hospital dyad using semi-structured interviews from a convenience sample of ICU (n = 19) and teleICU (n = 13) nurses. Interviews were analyzed using directed content analysis to identify themes that describe their experiences with teleICU using a deductive codebook developed from an expert consensus (American Association of Critical Care Nurses) AACN statement on teleICU nursing. Results Three themes were identified through the qualitative content analysis: [1] nurses described unique teleICU knowledge, including systems thinking and technological skills, [2] the teleICU partnership supported quality improvement initiatives, and [3] elements of the work environment influenced perceptions of teleICU and its use. When elements of the work environment, such as effective communication and role clarity, were not present, teleICU use was variable. Conclusions Flexible, provider-driven approaches for integrating teleICU services into daily practice may help define the future use of the teleICU model's applicability. Future work should focus on the importance of effective communication and role clarity in integrating the emerging teleICU services into teleICU/ICU practice.